A switch in disulfide linkage during minicollagen assembly in Hydra nematocysts - Engel, Ulrike; Pertz, Olivier Christian; Engel, Jürgen; Holstein, Thomas W. (The EMBO journal, 2001)
The smallest known collagens with only 14 Gly‐X‐Y repeats referred to as minicollagens are the main constituents of the capsule wall of nematocysts. These are explosive organelles found in Hydra, jellyfish, corals and other Cnidaria. Minicollagen‐1 of Hydra recombinantly expressed in mammalian 293 cells contains disulfide bonds within its N‐ and C‐terminal Cys‐rich domains but no interchain cross‐links. It is soluble and self‐associates through non‐covalent interactions to form 25‐nm‐long trimeric helical rod‐like molecules. We have used a polyclonal antibody prepared against the recombinant protein to follow the maturation of minicollagens from soluble precursors present in the endoplasmic reticulum and post‐Golgi vacuoles to the disulfide‐linked insoluble assembly form of the wall. The switch from intra‐ to intermolecular disulfide bonds is associated with ‘hardening’ of the capsule wall and provides an explanation for its high tensile strength and elasticity. The process is comparable to disulfide reshuffling between the NC1 domains of collagen IV in mammalian basement membranes.